Pemanfaatan Abu Terbang Batu Bara (Fly Ash) Sebagai Bahan Batako Yang Ramah Lingkungan - L, Arif Hamidi; Aman, Aman; Drastinawati, Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The use of coal as fuel in industry gives rise to waste such as fly ash and bottom ash. Fly ash has high content of silica and alumina thus can be potentially utilized as construction materials. Fly ash also contains heavy metals of 8.95 ppm Pb , 5.375 ppm Cu and 7.798 ppm Cr. Disposal of this waste in the ash lagoon or stacked inside the industrial area poses a problem for the environment. In this study, fly ash is utilized as raw material for making brick with cement composition to sand ratio 1:6 and replacement of sand by weight of fly ash with variation of 10 , 20 , 30 , 40 % . Compressive strength and leaching test were conducted after 28 days. The result of compressive strenght test showed that block with a variation of 0 % fly ash produces compressive strength of 115 kg/cm2 , 10 % of 155 kg/cm2 , 20 % of 120 kg/cm2 , 30 % of 120 kg/cm2 , 40 % at 95 kg/cm2. TCLP test results showed that most of the heavy metal content of Pb , Cu and Cr are immobilized so well that fly ash can be used as a mixture of brick that are safe for the environment. Keyword : fly ash, soldifikasi, batako